Design and fabrication of smart plate container / Muhammad Syauqi Ahmad Saiful Anuar - Ahmad Saiful Anuar, Muhammad Syauqi (2023)
The final year project of mine are to the design and fabricate of an Smart Plate Container. In order to overcome these difficulties, the Smart Plate Container has mechanical mechanisms that maximise storage capacity and make it simple to access goods that are kept. The major aim of completing the project is to produce a device that can transform the way plate are stored and managed. The container consists spring and slider that can accommodate plate systematically take by user. Through simple mechanical adjustments, users can create a tailored storage solution that suits their specific needs. The Mechanical Plate Container is engineered with a user-friendly design, making it easy to load and unload plates without causing damage or displacing other items. The mechanical mechanisms ensure smooth and controlled movements, minimizing the risk of accidents or breakages.